REFLEKSJA NAD DZIAŁANIEM A TOŻSAMOŚĆ SPOŁECZNA NAUCZYCIELA WE WSPÓLNOCIE PRAKTYKÓW - Ciepiela, Kamila (Neofilolog, 2019)
This article aims to discuss the problem of a relationship between reflection and identification in the community of EFL teaching practitioners. The basic tenet is that reflection enables individuals to construct and supply reification to community knowledge, which, in turn, allows for their identification as legitimate members of the community. Identity is neither static nor pre-given. It is built as one moves through life and changes according to one’s environmental needs, one’s interests and interactions. To expound and exemplify these tenets, two samples of conversations in a community of language teaching practitioners are analyzed. The analysis aspires to reveal a dialectic relationship between the processes of reflection and identification.